O językowej tożsamości człowieka w kontekście dyskursu religijnego - Zarzycki, Łukasz (Słowo. Studia językoznawcze, 2014)
The relationships between language and religious identity have been investigated so far using a variety of interdisciplinary sciences. However, very little emphasis has been put on the research related to the use of language in the religious aspect as it refers to the creation of one’s identity. This paper is based on the theoretical foundations of sociological theory of language (Sapir, Whorf, Luckmann, Berger). The author suggests the use of the sociology of language and religion together with discourse analysis to examine religious language community (here Protestantism).